(untitled) (Bangladesh Journal of Animal Science, 2022)
This study was conducted to investigate the changes in morphology, biomass yield, chemical composition and production cost of Hydroponic Wheat Fodder (HWF) with the advancement of growing days. The HWF was cultivated at low cost sprouting house at the Bangladesh Agricultural University (BAU) Dairy Farm, Mymensingh, Bangladesh. Firstly, wheat grains were collected, washed and then soaked in tap water for 12 h. Thereafter, grains were wrapped with a gunny bag for 24 h for germination. Then, grains were spread out in trays and irrigated using tap water up to 8th day morning. Biomass yield, morphological, nutritional parameters and cost of production were determined daily from each of the eight batches (day, 0 to 8) in the sprouting house. An increasing trend was seen in biomass yield, plant height, root length and root number of HWF with the days of advancement and found highest on 8th day (p=0.000). Biomass yield was increased 6 times during this 8 days cycle. On the contrary, a decreasing trend was observed in cost of production (0-5th day) and found lowest (BDT. 5.00) value in day 6th -8th (p < 0.001). A strong positive (r=0.891-0.989) correlation exists between biomass yield and morphological features (p < 0.001). Whereas, cost of production negatively (r=-0.857–0.946) correlated with biomass yield and morphological parameters (p < 0.001). The dry matter content of HWF reduced (p <0.001) gradually from day 0 to 8. The crude protein, ether extracts and minerals (calcium, phosphorus and magnesium) content of HWF increased positively from day 0 to 8 but nitrogen-free-extracts and organic matter declined (p < 0.001) gradually. However, morphology, biomass yield, chemical composition and production cost of fodder were similar between the days of 7 to 8. Finally, farmers might grow HWF up to 7-8 days as a new source of livestock feed. Bangladesh Journal of Animal Science, 51 (2): 68-80.